The effect of reproductive health education with stop motion video on children's knowledge - Nurcahyani, Lia; Padmawati, Rinela (Jurnal Kesehatan Ibu dan Anak, 2019)
Violence against children is public health, human rights, and social problem. The increase in cases of violence against children in Indonesia amounted to 91.2%. To prevent sexual violence, it is necessary to provide reproductive health education to children. Various media have been applied to early childhood education in reproductive health. The research objective is to find out the differences in reproductive health knowledge in groups with stop motion videos compared to songs. The research methods used nonrandomized quasi-experimental pre-test and post-test with control group design. The research was conducted in 2 playgroups in the working area of Sitopeng Public Heath Center, Cirebon, West Java from May to November 2017. The research subjects were 40 children, 20 children given stop motion video method, and 20 children given song method. There were significant differences in the knowledge of the pre-test and post-test for the stop motion group (Mean = 8.6; 95% CI = 7.27-9.92; P = 0.000) and the song (Mean = 1.8; 95% CI = 0.77-2.82; P = 0.002). There was a significant difference in knowledge changes in children's knowledge scores in the pre-test and post-test between the group of stop motion video media with the song media (Mean Difference = 6.80; 95% CI = 5.17-8.42; P = 0.000). Video stop motion is more effective in increasing reproductive health knowledge in children.